SmokeHaz: systematic reviews and meta-analyses of the effects of smoking on respiratory health - Jayes, Leah; Haslam, Patricia L.; Gratziou, Christina G.; Powell, Pippa; Britton, John; Vardavas, Constantine; Jimenez-Ruiz, Carlos; Leonardi-Bee, Jo (Elsevier, 2016)
Background: Smoking tobacco increases the risk of respiratory disease in adults and children, but communicating the magnitude of these effects in a scientific manner that is accessible and usable by public and policymakers presents a challenge. We have therefore summarised scientific data on the impact of smoking on respiratory diseases to provide the content for a unique resource, SmokeHaz.